Momentary predictors of a broad range of food parenting practices within a population-based sample of parents of preschool-aged children - Loth, Katie A.; Ji, Ziyu; Wolfson, Julian; Fisher, Jennifer; Berge, Jerica; Neumark-Sztainer, Dianne (Frontiers in Public Health, 2023)
The current study sought to understand the influence of momentary factors within the home and family environment, including parent stress, parent and child mood and child behaviors, on parents’ use of a broad range of food parenting practices later that same day. Ecological Momentary Assessment (EMA) was used to evaluate parents’ use of coercive, indulgent, structured and autonomy support food parenting practices, as well as numerous potentially salient momentary predictors, including parental stress, parent and child mood, and child behavior. Data were collected from 109 parents of preschool-aged children multiple times per day over the course of a ten-day data collection period, allowing for temporal sequencing of momentary predictors and use of food parenting practices. With some notable exceptions, study findings align with study hypotheses in that parent stress, parent and child low mood, and child negative behaviors early in the day were found to be associated with the use of less supportive food parenting practices later that same day. For example, greater parent negative mood earlier in the day was associated with a decrease in use of feeding practices from within the structure domain later on that same day (-2.5%, p<0.01), whereas greater parent positive mood earlier in the day was associated with an increase in use of structure later on that same day (+3.7%, p<0.01). Greater parent stress earlier in the day was associated with an increase in the use of coercive control (+3.2%, p<0.01) and indulgent (+3.0%, p<0.01) practices later that same day; surprisingly, a similar increase in stress earlier in the day was also found to be associated with an increase in the use of autonomy support (5.6%, p<0.01) feeding practices later on that same day. Developing an understanding of the types of momentary factors that influence a parent’s use of particular food parenting practices across multiple contexts is a crucial next step toward developing effective interventions aimed at teaching parents to use food parenting practices that are supportive of healthful child dietary intake and eating behaviors in a way that is responsive to shifting factors.